2019
DOI: 10.1080/25765299.2019.1585513
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the microdetermination of Para-aminophenol in generic brands of paracetamol tablets

Abstract: In Nigeria, paracetamol is readily available in several retail outlets where the conditions of storage can be poor leading to elevated levels of para-aminophenol (PAP), which is known to be nephrotoxic and hepatotoxic. However, the routine analysis of PAP is mostly by chromatographic separation which requires expensive instrumentation not often available in developing countries. The objective of this research was to develop a sensitive colorimetric method for the quantification of PAP in paracetamol. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…4. Although this result slightly differs from the 1:1 stoichiometric ratio obtained in our previous studies with chromotropic acid (Adegbolagun et al, 2018;Adegoke et al, 2019), there exists sufficient proof that furosemide hydrolyses in hydrochloric acid to yield an anthranilic derivative with a free amino acid group (Cruz et al, 1979). The primary aromatic amine can therefore be converted to the diazonium salt in the presence of nitrous acid and subsequently react with the activated ring system of chromotropic acid to generate the coloured azo adduct in a 1:1 ratio (Scheme 1).…”
Section: Stoichiometric Ratio Determination and Reaction Mechanismcontrasting
confidence: 59%
“…4. Although this result slightly differs from the 1:1 stoichiometric ratio obtained in our previous studies with chromotropic acid (Adegbolagun et al, 2018;Adegoke et al, 2019), there exists sufficient proof that furosemide hydrolyses in hydrochloric acid to yield an anthranilic derivative with a free amino acid group (Cruz et al, 1979). The primary aromatic amine can therefore be converted to the diazonium salt in the presence of nitrous acid and subsequently react with the activated ring system of chromotropic acid to generate the coloured azo adduct in a 1:1 ratio (Scheme 1).…”
Section: Stoichiometric Ratio Determination and Reaction Mechanismcontrasting
confidence: 59%
“…In a study conducted in Nigeria on paracetamol tablets that were obtained from the open markets, street vendors, and patent medicine stores, a higher content of para-aminophenol was found in samples. The storage and handling conditions in several retail outlets can be poor and far from the ideal recommendations of USP and BP, which state that paracetamol must be preserved in tight, light-resistant containers stored at room temperature and protected from moisture and heat [ 36 ]. Moreover, it has been reported that the shelf life of commercial paracetamol tablets decreases to 11.3% and 31.9% due to hydrolytic degradation to para-aminophenol following an increase in storage temperature from 25 to 37 °C at relative humidity of 75% and 100%, respectively [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the presence of p-AP in paracetamol samples may not only be a cause of therapeutic failure, but also may pose a safety issue, since p-AP has been shown to be significantly more potent than paracetamol as a nephrotoxicant in animal models [18]. The general method for determining p-AP levels is by spectrophotometry [19,20], and a Flow Injection Analysis (FIA) technique with a developed UV detector [21]. Since p-AP is an electroactive compound, its determination will be more selective by electrochemical methods.…”
Section: Introductionmentioning
confidence: 99%